2014
DOI: 10.1088/0953-8984/26/27/275901
|View full text |Cite
|
Sign up to set email alerts
|

Phonons and hybrid modes in the high and low temperature far infrared dynamics of hexagonal TmMnO3

Abstract: We report on temperature dependent TmMnO 3 far infrared emissivity and reflectivity spectra from 1910 K to 4 K. At the highest temperature the number of infrared bands is lower than that predicted for centrosymmetric P6 3 /mmc (D 6h 4 ) (Z=2) space group due high temperature anharmonicity and possible defect induced bitetrahedra misalignments. On cooling, at ~1600 ± 40 K, TmMnO 3 goes from non-polar to an antiferroelectric-ferroelectric polar phase reaching the ferroelectric onset at the ~700 K.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…For the samples YMnO 3 and TmMnO 3 , experimental values for two critical exponents (namely, α and β) are available. For YMnO 3 , experiments yielded α = −0.12 ± 0.01 [33] and β = 0.42 ± 0.03 [5], whereas for TmMnO 3 the estimates were α = −0.19 ± 0.01 [33] and β = 0.420 ± 0.001 [34]. It is important to note that both these critical exponents for both samples are reproducible by the present model by tuning only one parameter ρ in the theory.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…For the samples YMnO 3 and TmMnO 3 , experimental values for two critical exponents (namely, α and β) are available. For YMnO 3 , experiments yielded α = −0.12 ± 0.01 [33] and β = 0.42 ± 0.03 [5], whereas for TmMnO 3 the estimates were α = −0.19 ± 0.01 [33] and β = 0.420 ± 0.001 [34]. It is important to note that both these critical exponents for both samples are reproducible by the present model by tuning only one parameter ρ in the theory.…”
Section: Discussionmentioning
confidence: 49%
“…Numerical simulations [37] yielded α = +0. 34 and β = 0.25 for the chiral XY and α = +0. 24 and β = 0.30 for the chiral Heisenberg models.…”
Section: Introductionmentioning
confidence: 99%
“…This structure can be described as layers of MnO 5 bipyramids separated by Tm 3+ layers [ 11 ]. Wang et al [ 12 ] studied the ferroelectric behavior of hexagonal TmMnO 3 (h -TMO), reporting a ferro-paraelectric phase transition around 621 K, whereas, Yen et al [ 13 ] observed a magnetic transition around 84 K. Later, Massa et al [ 14 ] con rmed the electric and magnetic transitions showing a ferroelectric-magnetic coupling in the magnetically ordered phase using far-infrared emissivity and re ectivity measurements.…”
Section: Introductionmentioning
confidence: 99%